Fiscal Control Participatory: a strategy for effective territorial administration in Colombia (2015)
This essay on the participatory Fiscal Control as a strategy for the effective Territorial Administration in Colombia, is a reflection on citizen participation in the fiscal control as a relevant tool in the territorial entities which must be the best allies of the community to ensure that the various irregularities which comment on the use of public resources executed by different public and private sector entities they are minimized and he is achieved, thus the best results regarding the efficacy that can advance the administrations of the entities at the territorial level. So, citizen participation in the tax control is a tool that must be strengthened since the community has to be an active agent in the monitoring of the proper use of public resources. In this sense, participatory fiscal control is a strategy for effective territorial management in Colombia since it helps give best uses resources and achieve better results and therefore a better credibility of the Community institutions which exercise the fiscal control of the country. For this, note that these entities must forward their missionary exercise in a transparent, timely and impartial manner, thereby generating confidence in citizens who usually reports repeated manifestations of discontent in the use of public resources.